5G and beyond wireless networks technology, network deployments, and materials for antenna design - Singh, Indrasen; Tayal, Shubham; Pratap Singh, Niraj; Shankar Tripathi, Vijay; Singh, Ghanshyam (CRC Press, 2024)
"5G and beyond Wireless Networks: Technology, Network Deployments and Materials Used for Antenna Design offers a comprehensive overview of 5G and beyond 5G wireless network along with emerging technologies that support in design and development of networks. It also includes discussions on various materials used for practical antenna design which is suitable for 5G, beyond 5G applications, and Cell free massive MIMO systems. The book discusses the various latest techniques used in 5G and beyond 5G (B5G) communication, such as Non-Orthogonal Multiple Access (NOMA), Device to device (D2D) communication, 6G Ultra-Dense O-RAN, Rate-Splitting Multiple Access (RSMA), simultaneous wireless information and power transfer (SWIPT), massive Multiple Input Multiple Output (mMIMO), and cell free massive MIMO systems"--
Includes bibliographical references and index. - Description based on online resource; title from digital title page (viewed on April 02, 2024)
Keywords: 5G mobile communication systems; Communications mobiles 5G; COMPUTERS / Networking / General